PHYTOCHEMICAL SCREENING, In vitro ANTIOXIDANT AND GC-MS ANALYSIS OF Ziziphus mauritiana LEAVES EXTRACT - EUCHARIA EGBE, NKECHI; GARBA, SAIDU; ADAMU, ALIYU; ALIYU, FIRDAUSI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Ziziphus mauritiana (Z. mauritiana) is a plant known for its vast nutritional and pharmacological advantages. In the present investigation, leaf extracts of the plants with different solvents were analyzed by colorimetric methods for phytochemicals analysis, spectrophotometrically for the antioxidant activity by DPPH scavenging activity and gas chromatography-mass spectrometry (GC–MS) to identify the important functional groups and phytochemical constituents. The study observed the presence of some bioactive phytochemical constituents such as saponins, tannins, alkaloids, phenolics, terpenoids and flavonoids compounds. Colorimetric method suggested that, chloroform extract had the highest content of total phenolics (84.60 ± 0.92 μg GAE/mg of extract) while methanol extract contained higher content of total flavonoids (46.91±1.54 μg QE/mg of extract).Further, methanol extract exhibited higher DPPH free radical scavenging potential of 94.47% compared to ethyl acetate extract which showed the lowest activity of 70.34%.The GC– MS analysis detected the presence of 33 phytochemical compounds with diverse chemical structures from the different extracts. Major compounds identified in methanol, ethyl acetate, hexane and chloroform extracts were squalene (30.08%), salviolinic acid (12.55%), α-linolenic acid (26.42%) and palmitic acid (38.50%) respectively in addition to several other bioactive compounds.The results obtained in the present study suggest that leaves of Z. mauritiana can be used as a source for functional ingredients for pharmaceutical and food industries.